2015
DOI: 10.1111/jsm.12841
|View full text |Cite
|
Sign up to set email alerts
|

Pain Experienced During Vaginal and Anal Intercourse with Other-Sex Partners: Findings from a Nationally Representative Probability Study in the United States

Abstract: Introduction Recent U.S. nationally representative data indicate that about 30% of women and 5% of men reported pain occurring during their most recent sexual event; however, little is known about the severity, duration, or context of such pain, or its prevalence during vaginal vs. anal intercourse. Aims To document the prevalence and characteristics of pain during vaginal and anal intercourse among U.S. women and men (ages 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…Our findings add to a body of literature that, as described earlier, demonstrates a privileging of men's sexual pleasure, with women more often reporting lower levels of sexual pleasure and arousal, less frequent orgasm (Herbenick et al, 2010b), more frequent pain (Herbenick et al, 2015) and, described here, more common experiences of frightening sex. Indeed, scholars have long described how women's economic and political insubordination impacts their sexual lives and opportunities (e.g., Tiefer, 2001), making them vulnerable to sex that feels scary, painful, or beyond one's ability to control or consent to (e.g., Bay-Cheng, 2010;Gavey, 2012;Tiefer, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings add to a body of literature that, as described earlier, demonstrates a privileging of men's sexual pleasure, with women more often reporting lower levels of sexual pleasure and arousal, less frequent orgasm (Herbenick et al, 2010b), more frequent pain (Herbenick et al, 2015) and, described here, more common experiences of frightening sex. Indeed, scholars have long described how women's economic and political insubordination impacts their sexual lives and opportunities (e.g., Tiefer, 2001), making them vulnerable to sex that feels scary, painful, or beyond one's ability to control or consent to (e.g., Bay-Cheng, 2010;Gavey, 2012;Tiefer, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Marston and Lewis (2014) noted participants’ normalisation of coercive, painful and unsafe sex in relation to HSAI and stressed the ‘need for harm reduction activities that included discussion about consent and mutuality’ (p.6). Herbenick et al (2015) explored the issue of pain during HSAI and noted the prevalence of pain was high in women (reported in 72% women and 15% of men) and yet most participants did not communicate their experience of pain with their partners. Benson et al (2019) reported personal pleasure as a reason for women engaging in AI but also noted a resistance to disclose AI history due to perceived negative societal opinion about this practice.…”
Section: Resultsmentioning
confidence: 99%
“…One potential explanation may be related to the finding that nearly half of women who engage in consensual anal sex report negative experiences (Rogala & Tydén, 2003). In a recent nationally representative sample, it was found that 72% of women reported pain during anal sex (Herbenick, Schick, Sanders, Reece, & Fortenberry, 2015). If consensual anal sex is regarded as a negative experience for many women (although certainly not the case for many consenting women), it is not surprising that anal rape is associated with more negative outcomes than other nonconsensual penetration experiences.…”
Section: Discussionmentioning
confidence: 99%